Studi Literatur: Faktor-Faktor yang Mempengaruhi Work-Life Balance - Oktufiani Dwi Wulansari (Universitas Ciputra Surabaya, 2023)
Abstract: The purpose of this study is to determine the factors that influence work-life balance. The research method used in this research is literature study, by collecting several sources of previous research that discusses the factors that influence work-life balance. The results of this study indicate that there are three factors that influence work-life balance, namely individual factors, organizational factors, and life factors. Many areas can be affected by work-life balance, where these areas will affect the growth of the organization and its employees. The results of this study are expected to provide an overview to companies, leaders, and employees regarding the factors that affect work-life balance, so that efforts can be made to improve it.